Katekese Keluarga Katolik dalam Semangat Amoris Laetitia: Kasih dan Harmoni Rumah Tangga - Yohanes, Santo (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2025)
This paper aims to explore the implementation of the spirit of Amoris Laetitia in Catholic family catechesis, focusing on how Pope Francis' teachings can strengthen the bonds of love and harmony in family life. The method used is a literature review, examining the document Amoris Laetitia as well as related literature on family catechesis, family values within the Catholic Church, and the principles of Pope Francis' teachings. The findings of the study show that Amoris Laetitia emphasizes the importance of love that binds marriage and family, encouraging spouses to support, understand, and love each other in all aspects of their lives. Additionally, the study reveals that open communication, forgiveness, and joint prayer are key elements in fostering peace and harmony within the household. In conclusion, the application of Amoris Laetitia in family catechesis provides highly relevant guidance for Catholic families to build households full of love, mutual respect, and dedication to faith. Through this approach, Catholic families can strengthen their internal relationships and become living witnesses of God's love in everyday life.